2013
DOI: 10.1155/2013/617251
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Is Associated with Serotonin Syndrome in a Patient Receiving Amitriptyline, and Fentanyl: A Case Report and Review of the Literature

Abstract: We report a unique case of an adverse interaction between the oxazolidinone antibiotic linezolid, the tricyclic antidepressant amitriptyline and the opioid analgesic fentanyl in a 68-year-old woman with advanced ischemic peripheral arterial disease and sepsis, under empirical antibiotic treatment. We also summarize the current relevant literature as identified via PubMed, EMBASE, and PsycINFO as well as reference sections of selected articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…A large number of case reports in the literature have reported SS with the use of linezolid. In some of these reported cases, SS developed when linezolid was either used in combination with antidepressants[ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] or used alone. [ 21 ] The index case developed SS in the absence of the use of concomitant antidepressants, and fulfilled the criteria of SS, as per both Sternbach's and Boyer's criteria for SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of case reports in the literature have reported SS with the use of linezolid. In some of these reported cases, SS developed when linezolid was either used in combination with antidepressants[ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] or used alone. [ 21 ] The index case developed SS in the absence of the use of concomitant antidepressants, and fulfilled the criteria of SS, as per both Sternbach's and Boyer's criteria for SS.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous reviews have compiled the available case reports/series reporting the association of linezolid with SS. [ 25 26 ] Various antidepressants which lead to SS when used along with linezolid include citalopram,[ 5 8 9 10 11 ] escitalopram,[ 4 ] fluoxetine,[ 12 13 ] sertraline,[ 7 14 ] venlafaxine,[ 15 16 ] bupropion,[ 17 ] duloxetine,[ 18 ] mirtazapine,[ 10 ] paroxetine,[ 19 ] and amitriptyline[ 5 20 ] and also some opioids which could lead to SS when used along with linezolid include meperidine,[ 27 ] fentanyl,[ 13 20 ] and methadone. [ 28 29 ] Among various case reports, SS has been most commonly reported with the use of combination of linezolid with citalopram and sertraline.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly from our Osmangazi Tıp Dergisi / Osmangazi Journal of Medicine Cilt/Vol 43 No 1, 2021 country, Şahiner et al (6) had reported a serotonin syndrome case, whom undergoing antidepressant therapy with the serotonin reuptake inhibitor (SSRI) group and after using of linezolid. Samartzis et al (7) had reported a case of an adverse interaction between linezolid, amitriptyline and analgesic fentanyl in a 68-year-old woman with advanced ischemic peripheral arterial disease and sepsis. Woytowish et al (8) reviewed the literature and identified 32 documented serotonin toxicity cases, including 3 fatalities due to linezolid plus other serotonergic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic-induced delirium could occur by interaction with other medications, opioids with serotonergic properties, and/or kappa-opioid agonism [309]. Fentanyl and/or methadone may interact with linezolid or other monoamine oxidase inhibitors (MAOI) or serotonergic medication resulting in serotonin syndrome [310][311][312][313][314][315][316]. A retrospective review of 4538 patients treated with fentanyl and concurrent serotonergic agents suggests the incidence of serotonin syndrome was low [311], but prospective studies are needed before ignoring this ADR as there are many case reports suggesting a higher incidence [310][311][312][317][318][319][320][321][322].…”
Section: Analgesicsmentioning
confidence: 99%